Clinical features and 28-day mortality predictors of vaccinated patients admitted to a COVID-19 ICU hub in Italy - Claudia Stella; Cecilia Berardi; Annalisa Chiarito; Veronica Gennenzi; Stefania Postorino; Donatella Settanni; Melania Cesarano; Rikardo Xhemalaj; Eloisa Sofia Tanzarella; Salvatore Lucio Cutuli; Domenico Luca Grieco; Giorgio Conti; et al. (Journal of Anesthesia, Analgesia and Critical Care, 2023)
Abstract Background COVID-19 vaccination has been proved to be effective in preventing hospitalization and illness progression, even though data on mortality of vaccinated patients in the intensive care unit (ICU) are conflicting. The aim of this study was to investigate the characteristics of vaccinated patients admitted to ICU according to their immunization cycle and to outline the risk factors for 28-day mortality. This observational study included adult patients admitted to ICU for acute respiratory failure (ARF) due to SARS-CoV-2 and who had received at least one dose of vaccine. Results Fully vaccination was defined as a complete primary cycle from < 120 days or a booster dose from > 14 days. All the other patients were named partially vaccinated. One-hundred sixty patients (91 fully and 69 partially vaccinated) resulted eligible, showing a 28-day mortality rate of 51.9%. Compared to partially vaccinated, fully vaccinated were younger (69 [60–77.5] vs. 74 [66–79] years, p 0.029), more frequently immunocompromised (39.56% vs. 14.39%, p 0.003), and affected by at least one comorbidity (90.11% vs 78.26%, p 0.045), mainly chronic kidney disease (CKD) (36.26% vs 20.29%, p 0.035). At multivariable analysis, independent predictors of 28-day mortality were as follows: older age [OR 1.05 (CI 95% 1.01–1.08), p 0.005], history of chronic obstructive pulmonary disease (COPD) [OR 3.05 (CI 95% 1.28–7.30), p 0.012], immunosuppression [OR 3.70 (CI 95% 1.63–8.40), p 0.002], and admission respiratory and hemodynamic status [PaO2/FiO2 and septic shock: OR 0.99 (CI 95% 0.98–0.99), p 0.009 and 2.74 (CI 95% 1.16–6.48), p 0.022, respectively]. Conclusions Despite a full vaccination cycle, severe COVID-19 may occur in patients with relevant comorbidities, especially immunosuppression and CKD. Regardless the immunization status, predisposing conditions (i.e., older age, COPD, and immunosuppression) and a severe clinical presentation were predictors of 28-day mortality.